LITERASI INDUSTRI 4.0 UNTUK SISWA SMA MENUJU KEMERDEKAAN EKONOMI PASCA OTSUS ACEH - Ridha, Arrazy Elba; Pamungkas, Iing; Sofiyanurriyanti, Sofiyanurriyanti; Irawan, Heri Tri; Ulhaq, Riza; Ardiansyah, Muhammad; Akmal, Abdiel Khaleil (Universitas Mataram, 2025)
This Community Service Program (PKM) is implemented by Industrial Engineering Lecturers at Teuku Umar University as part of the implementation of the Tri Dharma of Higher Education, with a focus on empowering the youth of Aceh to face the challenges of industrial development following the expiration of the Special Autonomy Fund (Otsus) in 2027, which has played a crucial role in economic activities in Aceh Province. The critical role of the Otsus Fund for Aceh Province must be mitigated to minimise risks after the fund's expiration. The activity themed ‘Industry 4.0 Literacy for High School Students Toward Economic Independence Post-Otsus Aceh’ aims to equip participants with the knowledge to enhance local industrial growth through a more efficient Industry 4.0 approach. Through interactive lectures, structured discussions, and question-and-answer sessions using a pretest-posttest measurement approach, the PKM team can assess improvements in understanding across three critical pillars: understanding Industry 4.0, the Aceh Special Autonomy Fund and the economy, and digital technopreneurship based on local strengths. The community service activity involved 40 students from Calang 1 Public High School, consisting of both female and male students, using a pretest and posttest approach that contained information about the three critical pillars. Technically, the questions on the pretest and posttest were made different in order to obtain objective results. The measurement of ability was carried out for 5 hours, using the Growth Rate Analysis approach, the results showed a 92% increase in learning outcomes, with the average pretest score of 38.2 improving to an average posttest score of 73.3, focusing on topics related to digital transformation and economic independence in Aceh. This programme not only fulfils educational objectives but also instils an entrepreneurial mindset based on Industry 4.0 for the next generation of Aceh.